Choline Kinase Active Site Provides Features for Designing Versatile Inhibitors - Serran-Aguilera, L.; Nuti, R.; Lopez-Cara, L.C.; Rios-Marco, P.; Carrasco, M.P.; Marco, C.; Entrena, A.; Macchiarulo, A.; Hurtado-Guerrero, R. (Current Topics in Medicinal Chemistry, 2014)
Choline kinase (CK) is a homodimeric enzyme that catalyses the transfer of the ATP γ-phosphate to choline, generating phosphocholine and ADP in the presence of magnesium. Several isoforms of CK are present in humans but only the HsCKα has been associated with cancer and validated as a drug target to treat this disease. As a consequence a large number of compounds based on Hemicholinium (HC-3) have been described. Two compounds, previously reported to inhibit the human enzyme, have recently been shown to inhibit P. falciparum CK (PfCK) and therefore their potential applications might be anticipated to other pathogens. Herein, using molecular dynamic simulations, we have firstly observed that the ATP and the choline binding site of different CK in pathogens and human are conserved, suggesting that previous compounds inhibiting the human enzyme may also interact with CKs from different pathogens. We have substantiated such observation with experimental assays showing that HsCKα1, PfCK and CpCK bind to two compounds with distinct structural features in the low μM range. Collectively, these results uncover similarities among the choline kinase binding site from different pathogenic species and the human enzyme, highlighting the feasibility of designing novel inhibitors based on the choline binding pocket.
Keywords: Inhibition